Prevalensi Kejadian dan Pola Pengobatan Tuberkulosis pada Pasien HIV/AIDS di RSUD Kota Bandung: Tuberkulosis pada Pasien HIV/AIDS - Yani Mulyani; Raden Roro Maryana Ulfah; Rizki Siti Nurfitria (Jurnal Kesehatan Komunitas, 2019)
HIV causes a decrease in immunity which makes the patient susceptible to opportunistic infections such as tuberculosis. This research aims to find out the prevalence, patient descriptions’, treatment pattern and therapeutic goals for tuberculosis in HIV/AIDS patients who were taking the medication in polyclinic of DOTS and polyclinic of VCT in Regional General Hospital Of Bandung City. This was nonexperimental research. Data was collected retrospectively with cross-sectional approach using secondary data which were TB-01 form and HIV Care Summary Form and Antiretroviral Therapy from 1 January 2016 to 31 December 2018. From 668 Tuberculosis occurrence, there were 25 patients suffered HIV/AIDS. Result obtained the most risk factors was homosexual (60%), with the most ART treatment combination were Tenofovir, Lamivudine, and Evarirenz, 4% has a drug allergic, the most TB treatment history was new case (92%), with the most kind was pulmonary TB (56%), the most Anti TB treatment was category I (92%) and 60% patients done with full therapy